Personality Functioning and Peer Social Rebuff in Adolescence: Examining Interactions Over a Two-Year Period - Grigaitė, Agnė; Smolskaitė, Paulina; Gaudiešiūtė, Elena; Skabeikytė-Norkienė, Gabrielė; Barkauskienė, Rasa (Psichologija, 2025)
As the conceptualization of personality disorders has evolved and the dimensional model of personality disorder has gained prominence, personality functioning – defined as the self and interpersonal processes on a continuum from adaptive to impaired – has become a key aspect of personality psychopathology. Adolescence, a period of significant change, is associated with an increased risk of emerging personality disorders and a greater importance of peer relationships. Negative peer experiences, such as social rebuff, can be reciprocally linked to personality development. This study examined the bidirectional relationship between personality functioning and social rebuff in a sample of 855 adolescents (aged 11–18) using three measurements over two years. Personality functioning was assessed with the Levels of Personality Functioning Questionnaire 12–18 (LoPFQ 12–18), whereas social rebuff experiences were measured by using the Multidimensional Peer Victimization Scale (MPVS). The results showed moderate to high stability in both constructs. Social rebuff measured at the baseline predicted personality functioning difficulties one year later only. In contrast, personality functioning consistently predicted social rebuff throughout the study. These findings highlight the significant role of personality functioning in adolescent development and its link to peer interactions, which are particularly important during adolescence.
Keywords: level of personality functioning; peer victimization; social rebuff; adolescence